2000
DOI: 10.1080/026870300401414
|View full text |Cite
|
Sign up to set email alerts
|

Giving information: The importance of context on communicative opportunity for people with traumatic brain injury

Abstract: This study is one of a series investigating everyday communication skills of people with traumatic brain injury (TBI) using communication partners other than speech pathologists or research assistants. The ®rst of these studies examined telephone conversations where subjects were asked to request speci®c information during telephone interactions with a range of communication partners. Results indicated that people with TBI were disadvantaged in some of their interactions on the telephone with community agencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 33 publications
(19 reference statements)
0
21
0
Order By: Relevance
“…Dave described himself in this manner. However, as previously reported by Togher [52], he suggested that his passive communication style was context specific. When communicating with a friend who did not dominate the conversation he was able to take the role of the talker.…”
Section: Discussionmentioning
confidence: 66%
“…Dave described himself in this manner. However, as previously reported by Togher [52], he suggested that his passive communication style was context specific. When communicating with a friend who did not dominate the conversation he was able to take the role of the talker.…”
Section: Discussionmentioning
confidence: 66%
“…Factors that would be taken into account in consideration of a client's communication environment include people with whom a client has the opportunity or inclination to interact, physical and emotional environments in which interaction takes place and the combination of daily routines and significant events that make up people's lives (Togher, 2000;Ylvisaker, 2003).…”
Section: Figurementioning
confidence: 99%
“…For example, the interpersonal linguistic resources of people with aphasia (Ferguson, 1992; and people with traumatic brain injury (TBI) (Togher and Hand 1998) has been explored. Togher has also investigated the conversational interactions of people with TBI (Togher, Hand, and Code, 1999;Togher, 2000;. SFL has also been applied in the areas of dementia (Mortensen, 2005); acquired language disorder in children (Rigaudeau-McKenna, 2005), developmental language disorder in children (Thomson, 2005), attention deficit hyperactivity disorder (ADHD) (Mathers, 2005), and Asperger's Syndrome (Bartlett, Armstrong, and Roberts, 2005).…”
Section: Introductionmentioning
confidence: 98%